Incorporating spectroscopic on-line monitoring as a method of detection for a Lewis cell setup. Issue 13 (7th June 2017) - Heller, Forrest D.; Casella, Amanda J.; Lumetta, Gregg J.; Nash, Kenneth L.; Sinkov, Sergey I.; Bryan, Samuel A.
Abstract : A Lewis cell was designed and constructed for investigating solvent extraction systems by spectrophotometrically monitoring both the organic and aqueous phases in real time. Abstract : A Lewis cell was designed and constructed for investigating solvent extraction systems by spectrophotometrically monitoring both the organic and aqueous phases in real time. This new Lewis cell was tested and shown to perform well compared to other previously reported Lewis cell designs. The advantage of the new design is that the spectroscopic measurement allows determination of not only metal ion concentrations, but also information regarding chemical speciation – information not available with previous Lewis cell designs. For convenience, the new Lewis cell design was dubbed COSMOFLEX (COntinuous Spectroscopic MOnitoring of Forrest's Liquid–liquid EXtraction cell). After construction performance testing was done for establishing the ideal stir speed range, UV-Vis measured concentration and D value determination. Each one of these tests was satisfactorily passed.